Exploring the Role of Contextual Learning in Developing the Cognitive Abilities of Children Aged 5–6 Years - Ni Wayan Siti Nurani; Fitriana Fitriana; Sita Awalunisah; Shofiyanti Nur Zuama (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to explore the role of contextual learning in developing children’s cognitive abilities. The subjects of this research were all 18 children in Group B of Pelita Hati Kindergarten, consisting of 9 boys and 9 girls. The findings revealed that contextual learning played a significant role in enhancing the cognitive development of children in Group B, particularly through the use of spinach as a learning medium. Before the learning activity began, the teacher introduced spinach, explained its parts, and encouraged the children to identify and count them. The teacher then invited the children to play a sorting game by arranging the spinach from the smallest to the largest. Through contextual learning, children were able to interact directly with concrete materials, which supported the early childhood education principle of learning through play and facilitated better understanding. Observations conducted over three weeks showed that contextual learning greatly contributed to children’s cognitive growth, particularly in three key aspects: sequencing, identifying, and counting.